Prospects of Tectona Grandis as a Feedstock for Biodiesel - Sarin, Amit; Singh, Meetu; Sharma, Neerja; Singh, N. P. (Frontiers in Energy Research, 2017)
The limited availability of fossil fuels has encouraged the need of replacement fuels of renewable nature. Among the renewable fuels, biodiesel that produced from oil seeds and food wastes has been favored by the majority of researchers. In this study, Tectona Grandis seed oil has been investigated as a non edible feedstock for biodiesel. The oil content of seed is 43% which makes it suitable for commercial production of biodiesel. The production of biodiesel from Tectona Grandis oil was done with transesterification reaction giving high percentage yield of biodiesel which reached to 89%. The Tectona Grandis biodiesel was subjected to determine various physicochemical parameters by standard testing methods and found in agreement with the ASTM D 6751 and EN 14214 standards. The fatty acid methyl ester composition for the biodiesel is composed of 42.71% oleic acid, 13.1% palmitic acid and 31.51 % linoleic acid.. The biodiesel showed low oxidation stability which is attributed to high percentage of unsaturation. To address this issue, synthetic antioxidants were added to increase its resistance towards oxidation. By considering all the parameters, present study reveals that the Tectona Grandis seed oil is reliable for the production of biodiesel with encouraging probability in future.